Encompassing and Rational Expectations: How Sequential Corroboration Can Imply Refutation. - Ericsson, N; Hendry, D (Springer-Verlag, 1999)
Even though pieces of empirical evidence individually may corroborate an economic theory, their joint existence may refute that same theory. Testing of rational expectations models provides a concrete illustration of this principle. Surprisingly, empirical refutation of a rational expectations model may occur without having to estimate that model, and the refutation may be for a large class of expectations-based models and not just for a particular model specification. Narrow money demand in the United Kingdom illustrates such refutation. The general proposition concerning corroboration and refutation strongly favors the building of empirical models that are consistent with all available evidence.